Private Activity in Energy Remained Stable in 2006 - World Bank (Washington, DC, 2012)
This note states that in 2006 the number of new energy projects with private participation, along with the associated investment commitments, remained at levels similar to those of the previous two years, according to just-released data from the Private Participation in Infrastructure Project Database.